Gender, Military Effectiveness, and Organizational Change : The Swedish Model - Egnell, Robert; Hojem, Petter; Berts, Hannes; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
Through extensive analysis of the Swedish Armed Forces this study explores the possibilities and pitfalls of implementing of a gender perspective in military organizations and operations. It established a number of important lessons for similar attempts in other countries and discusses the continued process of implementation in the Swedish military.
Keywords: Political science; International relations; International organization; Peace; Social policy; Sociology; Sex (Psychology).; Gender expression; Gender identity; Political Science and International Relations; Gender Studies; Conflict Studies; International Relations; International Organization